LEARNING USING E-MODULES TO IMPROVE LEARNING OUTCOMES TO UNDERSTAND TAPERED TURNING STUDENTS OF THE MACHINING ENGINEERING EXPERTISE PROGRAM CLASS XI SMKN 1 SEMARANG - Dimas Ary Setiawan; Muhammad Khumaedi (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of the use of e-modules on the learning outcomes of understanding tapered turning students of the Machining Engineering Expertise Program at SMKN 1 Semarang. The study uses a quantitative approach with quasi-experimental methods and nonequivalent control group design. The research sample consisted of an experimental class that used e-modules and a control class that used conventional learning. Data collection is carried out through tests, observations, and documentation. Data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and N-Gain analysis. The results of the study show that the e-modules developed meet the criteria of validity and reliability and are effectively used in learning. There was a significant difference in learning outcomes between the experimental class and the control class. In addition, the increase in student learning outcomes in the experimental class was in the high category. Thus, the use of e-modules is effective in improving learning outcomes to understand tapered lathes and can be used as an alternative digital learning media in the Machining Engineering Expertise Program.